2021
DOI: 10.1111/appy.12487
|View full text |Cite
|
Sign up to set email alerts
|

A quarter of century after: The changing ecology of psychiatric emergency services

Abstract: Introduction Previous studies demonstrated a trend of increasing common mental disorders among the Emergency Department (ED) visitors in Western countries. Little is known about the current conditions of the emergency psychiatric services in Asian countries. This study aims to survey the current epidemiology and the changing ecology of emergency psychiatry services in Taiwan. Methods A total of 804 psychiatry consultations were initiated at the ED during the 1‐year period from July 1, 2014 to June 30, 2015 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Increases between 1988 and 2014 in Taiwan were driven by visits related to trauma and stressor-related disorders, depressive disorders, and suicide attempts. 5 In contrast, in Denmark, the number of MSUD ED visits decreased from 1985 to 2012. 6 Where data are available, research in Canada appears to coincide with patterns observed in the USA, with upward trends primarily reflecting increases in anxiety disorders and substance use disorders.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%
See 3 more Smart Citations
“…Increases between 1988 and 2014 in Taiwan were driven by visits related to trauma and stressor-related disorders, depressive disorders, and suicide attempts. 5 In contrast, in Denmark, the number of MSUD ED visits decreased from 1985 to 2012. 6 Where data are available, research in Canada appears to coincide with patterns observed in the USA, with upward trends primarily reflecting increases in anxiety disorders and substance use disorders.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%
“…Increases between 1988 and 2014 in Taiwan were driven by visits related to trauma and stressor-related disorders, depressive disorders, and suicide attempts. 5 In contrast, in Denmark, the number of MSUD ED visits decreased from 1985 to 2012. 6 …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Australia, the number of ED visits concerning mental health issues increased between 2004/2005 and 2016/2017, largely due to psychoactive substance abuse which involves drugs or other substances that affect mood, awareness, thoughts, feelings, or behavior such as alcohol, caffeine, nicotine, and certain pain medicines, etc., followed by anxiety and mood disorders [ 8 ]. Between 1988 and 2014, Taiwan saw a rise in visits to ED associated with depression disorders, suicide attempts, as well as trauma and stressor-related disorders, which are emotional and behavioral problems that may be caused by childhood traumatic and stressful experiences [ 9 ]. On the basis of available data, research in Canada is consistent with trends in the USA, with anxiety disorders and substance abuse disorders showing the most upward trends [ 6 ].…”
Section: Introductionmentioning
confidence: 99%